Character and Temperament Dimensions in Subjects with Depressive Disorder: Impact of the Affective State on Their Expression - Bajraktarov, Stojan; Novotni, Antoni; Arsova, Slavica; Gudeva-Nikovska, Dance; Vujovik, Viktorija (Open access Macedonian journal of medical sciences, 2017)
BACKGROUND: The depression is a cross-cultural condition that occurs in all cultures and within all nations with certain specificities, even though there are some differences in its manifestation. The hereditary load is of major importance, but also the individual personality factors, in the form of risk factors, are associated with the occurrence of depression. Personality characteristics have a significant impact on the occurrence of the recurrent depressive disorder and the outcome of the treatment as well.AIM: To identify the specific personality traits in people with the recurrent depressive disorder and the impact of the affective state on them.METHODS: Three questionnaires were used: a general questionnaire, Beck's scale of depressive symptoms, and TCI-R (inventory for temperament and character).RESULTS: The most indicative differences in the dimensions are found in the Harm avoidance and the Self-direction dimensions, and most variable dimensions dependent on effective state are Novelty seeking and Reward dependence.CONCLUSION: The people with the recurrent depressive disorder have a different profile of personality traits (temperament and character) compared with the control group, and their characteristics depend on their current affective state.